Human Virus Genomes Are Enriched in Conserved Adenine/Thymine/Uracil Multiple Tracts That Pause Polymerase Progression - Ruggiero, Emanuela; Lavezzo, Enrico; Grazioli, Marco; Zanin, Irene; Marušič, Maja; Plavec, Janez; Richter, Sara N.; Toppo, Stefano (Frontiers in Microbiology, 2022)
DNA secondary structures that deviate from the classic Watson and Crick base pairing are increasingly being reported to form transiently in the cell and regulate specific cellular mechanisms. Human viruses are cell parasites that have evolved mechanisms shared with the host cell to support their own replication and spreading. Contrary to human host cells, viruses display a diverse array of nucleic acid types, which include DNA or RNA in single-stranded or double-stranded conformations. This heterogeneity improves the possible occurrence of non-canonical nucleic acid structures. We have previously shown that human virus genomes are enriched in G-rich sequences that fold in four-stranded nucleic acid secondary structures, the G-quadruplexes. Here, by extensive bioinformatic analysis on all available genomes, we show that human viruses are enriched in highly conserved multiple A (and T or U) tracts, with such an array that they could in principle form quadruplex structures. By circular dichroism, NMR and Taq polymerase stop assays we prove that, while A/T/U-quadruplexes do not form, these tracts still display biological significance since they invariably trigger polymerase pausing within two bases from the A/T/U tract. A bases display the strongest effect. Most of the identified A-tracts are in the coding strand, both at the DNA and RNA level, suggesting their possible relevance during viral translation. This work expands on the presence and mechanism of nucleic acid secondary structures in human viruses and provides a new direction for antiviral research.